Telehealth Usage During The Coronavirus Disease 2019 Pandemic: A Meta-Analysis - Akbar, Prima Soultoni; Putri, Santy Irene; Widiyanto, Aris; Atmojo, Joko Tri; Prisusanti, Retno Dewi; Ramadhanti, Tarisa Aulia (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The recent pandemic has increased telemedicine use tremendously, but it has also pronounced access gaps to telemedicine. This study aimed to investigate factors affecting patient use of telehealth during the Coronavirus Disease 2019 Pandemic. This article was created using a systematic review and meta-analysis study that searched for articles in electronic databases such as Science Direct, PubMed, and Google Scholar. Observational studies are included in full papers with a publication year until 2022 were searched for this study. The Review Manager 5.3 (RevMan) software was used to analyze the articles in this study. We observed heterogeneity with a random-effect model to analyze the effect size from each primary study, and the results were reported as an adjusted odds ratio (aOR) and corresponding 95 percent confidence interval (CI). A total of 9 articles reviewed in the meta-analysis (consisting of 4 articles in each variable) showed that patients whose primary language is non-English (aOR= 0.72; 95% CI= 0.59 to 0.87; p= 0.0008) and have Medicaid insurance English (aOR= 0.86; 95% CI= 0.77 to 0.97; p= 0.02) were less likely to use telemedicine compared to patients who speak English and utilize private insurance. Medication insurance and non-English as a preferred language reduced the likelihood of patients using telemedicine.